Greening vision: balancing clinical excellence and ecological sustainability in eye health - Lin, Bin; Tang, Jing; Liang, Wei; Shi, Peng; Li, Dong-kan (Frontiers in Public Health, 2025)
The rapid advancement of ophthalmic medicine has significantly improved global visual health but concurrently imposed substantial ecological costs, creating an environmental paradox between efficient treatment and sustainability. This review explores the multifaceted carbon footprint of ophthalmic practices through a three-dimensional analysis: spatially, revealing stark cross-national differences in surgical emissions; temporally, tracking the environmental impact of technological evolution from extracapsular cataract extraction to phacoemulsification and vitreous surgery; and technologically, highlighting the role of disposable instruments, biomaterials, and energy consumption. It further presents an innovation matrix for “green ophthalmology,” encompassing technological breakthroughs, process optimizations, and behavioral interventions. The review emphasizes the need to integrate the “triple bottom line” (clinical, economic, environmental) into practice and policy, proposing future directions such as blockchain-based certification systems and standardized environmental assessment tools. Ultimately, it calls for multi-level actions-from individual clinicians to global governance-to reconcile high-quality eye care with ecological sustainability.